8 A Rapid Chest Pain Assessment Pathway including High-Sensitivity Troponin T Testing has a Limited Effect on Length of Stay. (6th June 2015) - McNaughton, Edwina; Gamble, James; Orr, William; Hutchinson, Thomas; Eayrs, Katie
Abstract : Patients admitted with chest pain represent a major part of the workload of all acute hospitals. High-sensitivity troponin assays provide an opportunity to accelerate assessment of these patients as they can exclude MI earlier after symptom onset, avoiding the need to wait for a 12-hour sample. Both local and national priorities encourage increasing same-day discharge and reducing length of stay for low-risk patients with chest pain, and accordingly these were the metrics we investigated. Methods: We introduced a new pathway to the Chest Pain Assessment Unit of a busy District General Hospital. This combined high-sensitivity troponin T (hsTnT) testing at admission and 6 h after symptom onset with formalised clinical risk-assessment using the TIMI risk score combined with these serial troponin results. Hospital episode statistics data was used to identify and compare length of stay and discharge diagnosis. Median length of stay was compared using the Mann-Whitney U test, and the proportion of patients discharged on the same day with the Chi-squared test. Summary discharge diagnosis was available, and this was used to identify patients with diagnoses representing non-cardiac chest pain (NCCP). Results: Data on 5271 admissions over the preceding 2 years were used as a baseline, and compared to the 3234 patients admitted between March 2012 and September 2013 inclusive, who were assessed using the new pathway with paired hsTnT testing. 878 (33%) of these patients had a discharge diagnosis that was classed as non-cardiac chest pain. Median length of stay was significantly reduced both in all admissions, and in those with a diagnosis identifiable as NCCP from discharge data. Same day discharges were also increased in both populations, although this increase was statistically significant only in the whole population. The changes provided a net cost benefit to the unit of approximately £12500 per year, mainly driven by increased NHS Payment by Results tariffs for patients discharged on the same day, and despite increased costs for troponin testing. Conclusions: The introduction of a modified pathway for the assessment of chest pain including hsTnT testing was successful in decreasing length of stay and increasing the proportion of same-day discharges. This had positive financial implications for the unit and improved the quality of care provided. The magnitude of the effect was smaller than might have been hoped for, suggesting that multiple other factors influence length of stay.